2004
DOI: 10.1038/nature02553
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced synaptic plasticity in newly generated granule cells of the adult hippocampus

Abstract: Neural stem cells in various regions of the vertebrate brain continuously generate neurons throughout life. In the mammalian hippocampus, a region important for spatial and episodic memory, thousands of new granule cells are produced per day, with the exact number depending on environmental conditions and physical exercise. The survival of these neurons is improved by learning and conversely learning may be promoted by neurogenesis. Although it has been suggested that newly generated neurons may have specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

57
844
8
6

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,158 publications
(923 citation statements)
references
References 30 publications
57
844
8
6
Order By: Relevance
“…3B). These results support previous reports that young neurons in the DG exhibit a lack of GABAergic inhibition and are, therefore, more receptive to the induction of LTP (28)(29)(30)(31).…”
Section: Fear Conditioning In Glial Fibrillary Acidic Protein (Gfap)-supporting
confidence: 82%
See 1 more Smart Citation
“…3B). These results support previous reports that young neurons in the DG exhibit a lack of GABAergic inhibition and are, therefore, more receptive to the induction of LTP (28)(29)(30)(31).…”
Section: Fear Conditioning In Glial Fibrillary Acidic Protein (Gfap)-supporting
confidence: 82%
“…Single-cell recordings have demonstrated that young neurons are more excitable than mature granule cells because of properties such as an elevated resting membrane potential, high input resistance, and low-threshold calcium channel expression (29,31). In addition, young neurons (2-4 wk old) are not inhibited, and can in fact be depolarized, by GABAergic activity (30,32).…”
Section: Discussionmentioning
confidence: 99%
“…However, our data strongly supports the hypothesis that new neurons need to compete for synaptic partners to ensure proper integration and survival [22]. Interestingly, it has been shown that during the first 3-6 weeks after their birth, new granule cells are highly excitable and show a higher degree of plasticity compared to mature granule cells [17] [18] [19] [21]. This unique feature has been attributed to their special functional properties with emerging evidence supporting the idea that adult neurogenesis in the DG is not a process for mere cell replacement but that new neurons exert their function at least partially due to these special properties [37] [38] [39].…”
Section: Resultssupporting
confidence: 72%
“…During the phase of integration, newborn granule cells are highly excitable and remain so for approximately 6 weeks. This period of high cellular plasticity has been associated with unique functional properties of new neurons and may help new neurons to successfully integrate into the pre-existing circuit [17] [18] [19] [20] [21]. Indeed, it has been suggested that new neurons compete for synaptic partners allowing for stable integration and subsequent survival [22].…”
Section: Introductionmentioning
confidence: 99%
“…The formation of newly-generated neurons in the hippocampus is associated with learn and memory abilities (Song et al, 2002;Schmidt-Hieber et al, 2004). When subjected to DHA chronically, both the young and aged rats' learning ability is improved (Gamoh et al, 1999;.…”
Section: Discussionmentioning
confidence: 99%